2021
DOI: 10.3390/ijerph182312536
|View full text |Cite
|
Sign up to set email alerts
|

Trans Adults Amidst the COVID-19 Pandemic: Quality of Life, Pandemic Impact, and Vaccine Preferences

Abstract: The ongoing COVID-19 pandemic is disproportionately impacting marginalized communities, such as Black, Indigenous, and people of color (BIPOC), disabled individuals, and transgender/nonbinary (i.e., trans) individuals. As trans individuals may be multiply marginalized, it is necessary to examine within group differences among trans individuals of different genders, races, socioeconomic statuses, and abilities. This study examines the following research questions: (1) What is the quality of life of trans adults… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
(64 reference statements)
0
4
0
Order By: Relevance
“…In India, the Human Immunodeficiency Virus (HIV) Key Populations (KPs) comprise female sex workers (FSWs), men who have sex with men (MSM), transgender (TG) and transsexual (TS) persons 2 ) . Their status as marginalized population, impacts their accessibility and availability of social and healthcare services 3 , 4 , 5 ) . The COVID-19 pandemic has affected all populations worldwide, with already marginalized sections being the most affected groups.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In India, the Human Immunodeficiency Virus (HIV) Key Populations (KPs) comprise female sex workers (FSWs), men who have sex with men (MSM), transgender (TG) and transsexual (TS) persons 2 ) . Their status as marginalized population, impacts their accessibility and availability of social and healthcare services 3 , 4 , 5 ) . The COVID-19 pandemic has affected all populations worldwide, with already marginalized sections being the most affected groups.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of higher susceptibility to minority stressors and disproportionate psychological and financial burdens among sexual and gender minority (SGM) populations may reduce the adoption of COVID-19 vaccination and further exacerbate health disparities 8 , 9 ) . The majority of trans-adults expressed their willingness to receive COVID-19; however, barriers in accessing such vaccinations have also been highlighted 5 ) . Hence, it is of vital importance that vaccine uptake among these populations is studied in order to identify the determinants and potential gaps in service provision and coverage.…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic has also exacervated preexisting inequities and health disparities and inequities among TWC ( 22 24 ). Under president's Trump administration, the U.S. government invoke Title 42 of the Public Health Service Act, closing the U.S.-Mexico border to asylum seekers, non-essential travelers and implementing express deportations.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a recent analysis of the Behavioral Risk Surveillance System from 2017 to 2019 found that TNB are more likely to report poor physical and mental health when compared with their cisgender peers [13]. The historic mental health disparities combined with the additional stressor imposed by the Covid-19 pandemic and the restrictive measures to control the pandemic could further impact the psychosocial wellbeing of TNB individuals [14].…”
Section: Introductionmentioning
confidence: 99%